Pelatihan Perempuan Desa Pada Kerajinan Crochet Di Hanura Kabupaten Pesawaran - Susanti Susanti; Rieka Rahmadaniah (Jurnal Publika Pengabdian Masyarakat, 2019)
In Indonesia there are many woman made crochet, as a proof a lot of crochet craft sold by media online or by store. Therefore, the team dedicated to do the training of crochet to woman in Hanura village Pesawaran district. The reason of the team choose Hanura village that over a period or more than four decades Hanura village has many changed, start from transmigrate blueprint with the pattern and now develop to greater governance and become one of the best governance in Pesawaran district Lampung province. Recently, Hanura village start to showed many better activities especially for the woman, they activities likes PKK and Karang Taruna that created and learn how to build good organizational system for increase Hanura village. Because of that fact, the team would like to conduct the crochet training for the woman in Hanura village in order to added their skills and increase their finance for their family by the product from crochet. This activities hopes can help PKK activities for the better one. The used methods are preparation, training and evaluation. The result of the training is crochet product.Keywords: Training, Women’s village, Croche